Synthesis and photophysical properties of triphenylpyridine derivatives - Fontes, Luís Filipe Baptista (2019)
In this study, triphenylpyridine derivatives were synthetized and fully characterized, including their photophysical properties. The triphenylpyridine core presented fluorescence in solution with quantum yields that surpass anthracene’s, with compound [4-(2-(2-methoxyphenyl)-6-phenylpyridin-4-yl)-N,N-dimethylaniline] being the brightest. This study allowed to identify the importance of 2-(pyridin-2-yl)phenol moiety for achieving fluorescence in solid state and not in solution. Complexation of boron was attempted for 2-(pyridin-2-yl)phenol derivatives with boron trifluoride, however the complex was not stable in solution. Five derivatives were analysed by single crystal x-ray diffraction and their structural features were indicative of the possibility of solid-state emission with very weak intermolecular and intramolecular interactions. All derivatives presented solid-state fluorescence with three compounds showing potential for further solid-state luminescence studies.